Perceived competencies and training preferences of extension agents in the Muda Agriculture Development Authority, Malaysia - Hussain, Intan Norbaizura (2012)
Competency is knowledge, skills, abilities and behaviors required for successful performance of job duties (Mirabile, 1995). Extension agents play an important role in developing agriculture systems to overcome many problems. Therefore, competency of extension agent is essential in order to perform their job duties effectively. In addition, extension activity is one of the factors contribute to increase productivity of farmers. The goals of agriculture extension activity are to transfer technology effectively and to empower the farmers to be more self-reliant in order to achieve the objectives of their farming activities. Researchers have identified lack of proper balance between technical and professional competencies of extension agents as a common problem in the extension services of developing countries. Therefore, the purpose of this study is to identify the competency level of MADA’s extension agents and their training preferences. Adequate and appropriate training in this field are required in order to improve the competency of an extension agent in terms of knowledge, skills, practices and attitude. There are seven dimensions of competency required by extension agents namely planning in extension activities, implementing in extension activities, evaluating in extension activities, communication in extension activities, guiding in extension activities, farm management in extension activities and ICT in extension activities. Respondents from this study were 200 extension agents in MADA. They were consist of 26 Agriculture Officer (AO), 30 Agriculture Assistant Officer (AAO) and 144 Agriculture Assistant (AA). Data were collected using structured questionnaire. Likert type scale of 1 to 5 (1 representing very low and 5 representing very high); were used to measure respondents’ competency level and the importance of the seven competency dimensions. The questions asked included items such as their ability in handling a meeting, ability to monitor the farmers and ability to communicate with farmers and colleagues. Descriptive analysis and ANOVA were applied to analyze the data using SPSS. The findings show that the highest total mean in level of competency is implementing (4.37) and the least (3.69) is guiding. Meanwhile in level of importance, guiding shows the highest mean (4.50) and the least (4.31) is evaluating. Training preferences were asked using Likert type scale and results shows 99 percent of the respondents highly agreed with the given statements. Statement with the highest mean (4.79) is training is very important to improve skill and ability and statement with the lowest mean (4.26) is training in various field should be given to officer to perform their job. ANOVA was conducted to compare demographic factors with the seven dimensions of competency. Post hoc comparison reveals that there were significant differences between age, education and years of experience. However, the level of position shows no significant differences between AO, AAO and AA in their competencies level. Based from the findings, this study recommends MADA to carry out proper Training Needs Analysis to ensure the effectiveness of training for extension agent in the future. Demographic factors which show significant differences in term of competencies should be considered and used in planning training to the different extension agents. Additional research to replicate this study with other extension agents from other agency is needed to evaluate the extent to which the results presented here would be similar and recommendation will be applicable. The findings of this study hopefully can contribute to the success of the extension programs in MADA. Extension agents must be able to see their competency level and willing to improve themselves to perform well in their job duties.